2006
DOI: 10.1111/j.1365-2036.2006.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: rebound acid hypersecretion after therapy with proton pump inhibitors

Abstract: SUMMARY BackgroundThe occurrence and the clinical relevance of rebound acid hypersecretion after discontinuation of proton pump inhibitors is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 29 publications
0
36
0
3
Order By: Relevance
“…However, a similar result was not found in three different studies that examined patients who suddenly stopped PPI therapy while using it for GERD. Contrary to Lodrup's systematic literature review, Hunfeld reported in his systematic literature review that no significant rebound acid secretion occurred with the sudden cessation of PPIs in healthy volunteers (28).…”
Section: How Must the Drugs Used In The Treatment Of Gerd Be Stopped?mentioning
confidence: 91%
“…However, a similar result was not found in three different studies that examined patients who suddenly stopped PPI therapy while using it for GERD. Contrary to Lodrup's systematic literature review, Hunfeld reported in his systematic literature review that no significant rebound acid secretion occurred with the sudden cessation of PPIs in healthy volunteers (28).…”
Section: How Must the Drugs Used In The Treatment Of Gerd Be Stopped?mentioning
confidence: 91%
“…This along with the finding of non-inferiority at day 90 for Succeed® compared with omeprazole raises the question of whether omeprazole continues to result in acid suppression over a prolonged period of time. However, there is very limited strong evidence of rebound acid hypersecretion in humans following cessation of treatment with proton pump inhibitors for periods of longer than eight weeks [32].…”
Section: Discussionmentioning
confidence: 99%
“…Rebound acid hypersecretion due to the PPI break is possible, but most likely not important within the 4-day break used. 58,59 We believe that blinding of subjects to the test liquid used should assure unbiased results in terms of, eg, swallowing rate and heartburn. As a result of our chosen protocol, the random swallowing test was only performed in the upright position.…”
Section: Discussionmentioning
confidence: 99%